Nursing workload associated with neonatal mortality risk: a cross-sectional study - da Silveira, Raquel Rondina Pupo [UNESP]; Serafim, Clarita Terra Rodrigues [UNESP]; E Castro, Meire Cristina Novelli [UNESP]; Rodrigues, Gabrielle Maria [UNESP]; Corrente, José Eduardo [UNESP]; Lima, Silvana Andrea Molina [UNESP] (FapUNIFESP (SciELO), 2022)
Objectives: to analyze the association between nursing workload and neonatal mortality risk in newborns admitted to the Neonatal Intensive Care Unit. Methods: this is an observational, cross-sectional study conducted from January 2019 to January 2020. Results: the sample consisted of 399 newborns, 55.4% male, Nursing Activities Score mean of 67.5%, and Score for Neonatal Acute Physiology Perinatal Extension mean of 17.7, revealed itself as a predictor of the risk of death, while gestational age, length of hospitalization, and the first-minute Apgar established a protective relationship. The correlation between workload and neonatal mortality was low (r= 0.23, p=0.0009). Conclusions: the workload of the nursing team is not associated with the risk of mortality in the Neonatal Intensive Care Unit, as measured by the Nursing Activities Score.
Carga de trabajo de enfermería relacionada al riesgo de mortalidad neonatal: un estudio transversal
Carga de trabalho de enfermagem associada ao risco de mortalidade neonatal: um estudo transversal
Keywords: Mortality; Neonatal Nursing; Patient Acuity; Safety Management; Workload